The Analysis of Farmers' Financial Literacy and its' Impact on Microcredit Accessibility with Interest Subsidy on Agricultural Sector - Widhiyanto, Iman; Nuryartono, Nunung; Harianto, Harianto; Siregar, Hermanto (International Journal of Economics and Financial Issues, 2018)
The government of Indonesia has been rolling out the Food Security and Energy Credit (KKP-E) with interest rate subsidy since 2008 for the people who have no access to banking but have a feasible business. This study aims (1) to analyze the level and influence variables of respondents' financial literacy and (2) to analyze the variables that influence the farmers' accessibility to KKP-E. The methods used are multiple regressions and logistic analysis. The results show that the levels of financial literacy are in the medium categories, which variables affected consist of age, education duration, distance to the capital regency location, annual income, bank account ownership, and financial education experiences. The variables influence of KKP-E accessibility consists of farms' income, the width of the cultivated area, collateral, interest rate, financial literacy index, farmer group legal status, credit accessibility experiences, and loan amount. Financial literacy significantly influences the KKP-E accessibility. Keywords: agricultural, credit accessibility, financial literacy, interest rates subsidy JEL Classifications: G210; H250; Q140; Q180